1969
DOI: 10.1159/000179744
|View full text |Cite
|
Sign up to set email alerts
|

Studies on Glomerulotubular Balance During Aortic Constriction, Ureteral Obstruction and Venous Occlusion in Hydropenic and Saline-Loaded Rats

Abstract: Proximal glomerulotubular balance was examined in hydropenic rats and rats undergoing saline diuresis. Three experimental procedures were used to lower GFR: aortic constriction, ureteral obstruction and renal venous occlusion. During hydropenia all three manipulations lowered total GFR and nephron GFR, and prolonged transit-time, but did not significantly alter TF/P inulin ratios. Absolute reabsorption decreased proportionately to GFR and glomerulotubular balance was well maintained. Calculated tubular volume … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
17
0
1

Year Published

1971
1971
2013
2013

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(21 citation statements)
references
References 26 publications
3
17
0
1
Order By: Relevance
“…Because of the relatively high plasma protein concentration during hydropenia, changes in GFR induced by altering renal perfusion pressure will result in marked changes in the oncotic pressure of blood issuing from the glomerulus into peritubular capillaries, whereas similar changes in GFR during saline diuresis and a lower plasma protein concentration will produce only minor changes in postglomerular oncotic pressure. This might serve to explain why proximal glomerulotubular balance is precisely maintained in hydropenia and only partially maintained during saline diuresis (21).…”
Section: Results Are Summarized Inmentioning
confidence: 99%
“…Because of the relatively high plasma protein concentration during hydropenia, changes in GFR induced by altering renal perfusion pressure will result in marked changes in the oncotic pressure of blood issuing from the glomerulus into peritubular capillaries, whereas similar changes in GFR during saline diuresis and a lower plasma protein concentration will produce only minor changes in postglomerular oncotic pressure. This might serve to explain why proximal glomerulotubular balance is precisely maintained in hydropenia and only partially maintained during saline diuresis (21).…”
Section: Results Are Summarized Inmentioning
confidence: 99%
“…It seems unlikely that this relationship could be due to an effect of tubular distension on reabsorption as suggested by Gertz et al (4). It has been shown that during obstruction of individual tubules (12,27), as well as during partial ureteral obstruction (6,7), reabsorption fell at a time when tubular diameter was increased. We have made similar observations in this laboratory.3 Also, it seems unlikely that the coupling of load and reabsorption is mediated by an effect of delivery out of the proximal tubule to activate a feedback mechanism such as suggested by Leyssac (2).…”
Section: Details Of This Experiments Are Given Inmentioning
confidence: 91%
“…However, this concept cannot account for the presence of glomerulotubular balance when filtration rate is lowered by ureteral or renal venous obstruction which produce tubular distension at a time when reabsorption is decreased (6,7). Each of the above explanations for glomerulotubular balance involves some intraluminal effect of changes in the delivery of filtrate to bring about concordant changes in the rate of reabsorption.…”
Section: Introductionmentioning
confidence: 99%
“…In the normal rat, there is a considerable body of evidence which indicates that the proximal tubule is endowed with little intrinsic capacity for regulation of sodium and water reabsorption (34)(35)(36)(37)(38)(39)(40)(41)(42)(43) and that the control of APR is governed primarily by alterations in the peritubular transcapillary Starling forces (5)(6)(7)(8)(9)(10)(11)(12)(13)(14)28). The data obtained in the present study indicate that APR in rats with a moderate degree of NSN is likewise governed largely by the peritubular environment, and in particular, by the extent to which 7rE is reduced.…”
Section: Control Glomerulonephrltismentioning
confidence: 99%